Detection of Dengue Virus in Mosquito Extracts and Human Clinical Samples Using a Field Expedient Molecular Platform. Issue 9 (1st September 2015) - Pal, Subhamoy; Richardson, Jason H.; Murphy, Jittawadee R.; Krairojananan, Panadda; Kongtak, Patcharee; Jaichapor, Boonsong; Kankaew, Prasan; Ekanayake, Sajeewane; Davis, Timothy J.; Maserang, David L.; Teng, David H. F.; Crisp, Robert J.; et al.
ABSTRACT: Dengue fever occurs in localized outbreaks and can significantly erode troop strength and mission readiness. Timely identification of dengue virus (DENV) provides for rapid and appropriate patient management decisions, such as medical evacuation and supportive therapies, as well as help to promote Force Health Protection through vector control and personal protective measures. The "Ruggedized" Advanced Pathogen Identification Device is a field-friendly PCR (Polymerase Chain Reaction) platform that can be used to facilitate early identification of DENV. We developed a dry-format PCR assay on this platform. The assay demonstrated 100% analytical specificity for detecting dengue using a cross-reactivity panel. We used a panel of 102 acute, DENV isolation positive serum samples and 25 DENV negative samples; the assay demonstrated a clinical sensitivity of 97.1% (95% C.I. 91.6–99.4%) and specificity of 96.0% (95% C.I. 79.7–99.9%) in identifying patients with dengue infection. We also used the assay to test mosquito homogenates from 28 adult female Aedes aegypti . A single DENV infected mosquito was identified using the PCR assay and confirmed using immunofluorescence as a reference method. Much of the testing was performed under austere field conditions. Together, our results demonstrate the utility of this assay for detecting DENV in vector and human samples in field environments.